Trends in anti-Müllerian hormone concentrations across different stages of pregnancy in women with polycystic ovary syndrome - Köninger, Angela; Strowitzki, Thomas (Reproductive biomedicine online, 2018)
What are the trends in anti-Müllerian hormone (AMH) concentrations from pre-conception to the third trimester of pregnancy in women with polycystic ovary syndrome (PCOS)? Observational study including cross-sectional and longitudinal data analysis.
Gesehen am 04.12.2019